Exploring innovative moments in a brief integrative psychotherapy case study - Nasim, Ron (2019)
The present study examined the emergence of innovative moments in a successful case of Brief Integrative Psychotherapy (BIP) based on Hill's 3-stage model. Hill's model suggests that optimally therapeutic processes involve exploration (based on client-centered therapy), insight (based on psychoanalytic therapy), and action (based on behavioral therapy). Innovative moments are exceptions to the problematic pattern of meaning that brought the client to therapy. Previous studies showed that their occurrences in the therapeutic conversation were related to symptomatic improvement in different therapeutic models; nevertheless, they have not yet been explored in integrative psychotherapy, and especially psychotherapy that contains explicit psychodynamic components. The aim of the study was too examine the relations between innovative moments, on the one hand, and (a) symptomatic improvement, (b) therapist's interventions, and (c) client's subjective experience, session by session, on the other. A 12-session case study of a 27-year-old female client was coded according to the Innovative Moments Coding System. Outcome improvement was measured by the Outcome Questionnaire (OQ-45.2). Therapist's interventions were coded according to the Helping Skills Scale (HSS). The subjective experience for each session was measured by the Session Evaluation Questionnaire (SEQ). The findings suggest that innovative moments are related to symptomatic change. Exploration and insight interventions were related to the emergence of more elementary innovative moments, whereas action interventions were found to be related to more highly developed innovative moments. Finally, innovative moments were strongly associated with 3 out of the 4 dimensions of client's subjective experience of the session (depth, smoothness. and positivity). These results should he further explored at a sample level.